Desafios na formação do engenheiro-docente: novas DCNs, tecnologias da educação e da indústria 4.0 - Noga, Liliane (2021)
This dissertation is part of the Postgraduate Program in Education: Curriculum of the Pontifícia Universidade Católica de São Paulo, in the research line New Technologies in Education. It deals with the training of engineers for teaching in higher education and their preparation to learn about new technological concepts with their platforms and strategies oriented to projects and production, experienced in the reality of Industry 4.0, as well as concepts and techniques, methodologies and technologies called Education 4.0. Its objective is to show, in the researched works, how the formation of the teaching engineer was identified. With a qualitative approach methodology, three data production procedures were adopted: The first is to conduct a literature review of scientific productions on the subject; The second refers to the survey of articles from the annals of editions from 2004 to 2020 of the Brazilian Congress of Engineering Education (Cobenge), organized by the Brazilian Association of Engineering Education (Abenge). These reviews made it possible to identify the drivers, authors, and most used keywords, and the third, through a data survey on the e-MEC portal to map nine schools and their curricular matrices in teaching courses for Engineering. The theoretical foundation of this work has authors and researchers in the field of Education, among them, Gimeno Sacristán (2013) and Masetto (2010, 2012, 2018). Data analysis was performed through content analysis, based on studies by Bardin (1977). The courses surveyed identified, through the matrix created, that the lato sensu graduate programs approach the needs identified in the new DCNs, however, they are insufficient when preparing teachers to work with concepts and technologies from the fourth industrial and educational revolution. And the bibliographic survey demonstrates that there is a lack of training, with regard to didactic-pedagogical skills, that the university engineer teacher requires a long educational training